Mitochondrial Dysfunction: A Basic Mechanism in Inflammation-Related Non-Communicable Diseases and Therapeutic Opportunities - Anna Hernández-Aguilera; Anna Rull; Esther Rodríguez-Gallego; Marta Riera-Borrull; Fedra Luciano-Mateo; Jordi Camps; Javier A. Menéndez; Jorge Joven (Mediators of Inflammation)
Obesity is not necessarily a predisposing factor for disease. It is the handling of fat and/or excessive energy intake that encompasses the linkage of inflammation, oxidation, and metabolism to the deleterious effects associated with the continuous excess of food ingestion. The roles of cytokines and insulin resistance in excessive energy intake have been studied extensively. Tobacco use and obesity accompanied by an unhealthy diet and physical inactivity are the main factors that underlie noncommunicable diseases. The implication is that the management of energy or food intake, which is the main role of mitochondria, is involved in the most common diseases. In this study, we highlight the importance of mitochondrial dysfunction in the mutual relationships between causative conditions. Mitochondria are highly dynamic organelles that fuse and divide in response to environmental stimuli, developmental status, and energy requirements. These organelles act to supply the cell with ATP and to synthesise key molecules in the processes of inflammation, oxidation, and metabolism. Therefore, energy sensors and management effectors are determinants in the course and development of diseases. Regulating mitochondrial function may require a multifaceted approach that includes drugs and plant-derived phenolic compounds with antioxidant and anti-inflammatory activities that improve mitochondrial biogenesis and act to modulate the AMPK/mTOR pathway.